Hadith #2115 - Sunan Abi Dawud - Abdullah bin 'Utba; Khalas bin 'Amr al-Hajri خلاس بن عمرو الهجري; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
The aforesaid tradition has also been transmitted by ‘Alqamah on the authority of ‘Abd Allah. ‘Uthman (b. Abi Shaibah) narrated a similar tradition.
Grade: Sahih

Hadith #3560 - Sunan Abi Dawud - al-Hasan al-Basri الحسن البصري; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Samra bin Jundub; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
‘Umra’ means that a man says to another man: It belongs to you so long as you live. When he says that, it belongs to him and to his heirs. Ruqba means that a man says to another: From me and from you.
Grade: Hasan

Hadith #3612 - Sunan Abi Dawud - Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; Abu Musa al-Asha'ari; Muhammad bin al-Minhal al-Darir محمد بن المنهال الضرير; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Sa'id bin Abi Barda سعيد بن أبي بردة; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) sent an army to Banu al-Anbar. They captured them at Rukbah in the suburbs of at-Ta’if and drove them to the Holy Prophet (ﷺ). I rode hurriedly to the Holy Prophet (ﷺ) and said: Peace be on you, Messenger of Allah, and the mercy of Allah and His blessings. Your contingent came to us and arrested us, but we had already embraced Islam and cut the sides of the ears of our cattle. When Banu al-Anbar arrived, the Holy Prophet (ﷺ) said to me: Have you any evidence
Grade: Da'if

Hadith #3615 - Sunan Abi Dawud - Abu Hurairah; Abu Rafi'; Khalas bin 'Amr al-Hajri خلاس بن عمرو الهجري; Muhammad bin al-Minhal al-Darir محمد بن المنهال الضرير; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Qatadah through a different chain of narrators to the effect that two men laid claim camel and both of them produced witness so the prophet (peace be upon him) divided it in halves between them.
Grade: Hasan

Hadith #3804 - Sunan Abi Dawud - ibn Abbas; Maymun bin Mahran ميمون بن مهران; Muhammad bin Abi 'Adi محمد بن أبي عدي; Muhammad bin Bashar Bindar محمد بن بشار بندار; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan Abi Dawud)
The Prophet (ﷺ) said: Beware, the fanged beast of prey is not lawful, nor the domestic asses, nor the find from the property of a man with whom treaty has been concluded, except that he did not need it. If anyone is a guest of people who provide no hospitality for him, he is entitled to take from them the equivalent of the hospitality due to him.
Grade: Sahih

Hadith #3937 - Sunan Abi Dawud - Abu Hurairah; al-Nadr bin Anas bin Malik النضر بن أنس بن مالك الأنصاري; Ali bin al-Madini علي بن المديني; Bashayr bin Nahayk بشير بن نهيك السدوسي; Muhammad bin Bashr bin al-Farafsa محمد بن بشر بن الفرافصة العبدي; Nasr bin 'Ali bin Nasr bin 'Ali; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
If anyone emancipates a share in his slave, he should completely emancipate him if he has money; but if he has none, then slave will be required to work (to pay for his freedom), but he must not be overburdened.
Grade: Sahih

Hadith #4047 - Sunan Abi Dawud - al-Hasan al-Basri الحسن البصري; Imran bin Husain; Mkhld bin Khalid bin Yazid مخلد بن خالد بن يزيد الشعيري; Qatada قتادة; Ruh bin 'Ubada bin al-'Ala' روح بن عبادة بن العلاء; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة (Sunan Abi Dawud)
The king of Rome presented a fur of silk brocade to the Prophet (ﷺ) and he wore it. The scene that his hands were moving (while wearing the robe) is before my eyes. He then sent it to Ja’far who wore it and came to him. The Prophet (ﷺ) said: I did not send it to you to wear. He asked: What should I do with it? He replied: Send it to your brother Negus.
Grade: Da'if

Hadith #4055 - Sunan Abi Dawud - Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Anas ibn Malik; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة (Sunan Abi Dawud)
It is only a garment wholly made of silk which the Messenger of Allah (ﷺ) forbade, but there is no harm in the ornamented border and the wrap.
Grade: Sahih

Hadith #4131 - Sunan Abi Dawud - Abu al-Malih; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Usama bin 'Umayr al-Hadhali; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
Al-Miqdam ibn Ma’dikarib and a man of Banu Asad from the people of Qinnisrin went to Mu’awiyah ibn AbuSufyan. Mu’awiyah said to al-Miqdam: Do you know that al-Hasan ibn Ali has died? Al-Miqdam recited the Qur’anic verse “We belong to Allah and to Him we shall return.” A man asked him: Do you think it a calamity? He replied: Why should I not consider it a calamity when it is a fact that the Messenger of Allah (ﷺ) used to take him on his lap, saying: This belongs to me and Husayn bel
Grade: Sahih

Hadith #4413 - Sunan Abi Dawud - al-Hasan al-Basri الحسن البصري; Htan bin 'Abdullah حطان بن عبد الله الرقاشي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Ubada bin As-Samit; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Qur’anic verse goes: “If any of your woman are guilty of lewdness, take the evidence of four (reliable) witnesses from amongst you against them, and if they testify, Confine them to houses until death do chain them or Allah ordains for them some (other) way. Allah then mentioned man after woman and combined them in another verse : “If two men among you are guilty of lewdness, punish them both. If they repent and amend, leave them alone. This command was abrogated by the verse relating
Grade: Hasan

Hadith #4479 - Sunan Abi Dawud - Abdullah bin Fyrwz عبد الله بن فيروز الداناج; Ali ibn Abi Talib; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) gave a beating with palm-branches and sandals for drinking wine and Abu Bakr gave lashes. When ‘Umar came to power, he called upon people and said to them: The people are living now near watering placing, and, according to Musaddad’s version, “near villages and watering places, so what do you say about the punishment for (drinking) wine? ‘Abd al-Rahman b. ‘Awf said: We think that you should prescribe the lightest punishment. So he fixed eight lashes for it. Abu Dawud
Grade: Sahih

Hadith #4515 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Sa'id bin 'Amir al-Dab'ai سعيد بن عامر الضبعي; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة (Sunan Abi Dawud)
The Prophet (ﷺ) Said: If anyone kills his slave, we shall kill him, and if anyone cuts off the nose of his slave, we shall cut off his nose.
Grade: Da'if

Hadith #4528 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; al-Hasan al-Basri الحسن البصري; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Qatada قتادة; Qays bin 'Aabad al-Qaysi قيس بن عباد القيسي الضبعي; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
A Jew killed a girl of the Ansar for her ornaments. He then threw her in a well, and crushed her head with stones. He was then arrested and brought to the Prophet (ﷺ). He ordered regarding him that he should be stoned to death. He was then stoned till he died. Abu Dawud said: It has been transmitted by Ibn Juraij from Ayyub in a similar way.
Grade: Sahih

Hadith #4554 - Sunan Abi Dawud - Abdah bin Sulaiman al-Klabi عبدة بن سليمان الكلابي أبو محمد الكوفي; Abu Musa al-Asha'ari; Ghalb bin Mhran غالب بن مهران; Hameed bin Hilal حميد بن هلال; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة (Sunan Abi Dawud)
About the bloodwit for quasi-intentional murder….. He then mentioned a similar tradition as mentioned above.
Grade: Sahih

Hadith #4649 - Sunan Abi Dawud - Anas ibn Malik; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
AbdurRahman ibn al-Akhnas said that when he was in the mosque, a man mentioned Ali (may Allah be pleased with him). So Sa’id ibn Zayd got up and said: I bear witness to the Messenger of Allah (ﷺ) that I heard him say: Ten persons will go to Paradise: The Prophet (ﷺ) will go to Paradise, AbuBakr will go to Paradise, Umar will go to Paradise, Uthman will go to Paradise, Ali will go to Paradise, Talhah will go to Paradise: az-Zubayr ibn al-Awwam will go to paradise, Sa’d ibn Malik will go t
Grade: Sahih

Hadith #5188 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Abu Hurairah; Abu Rafi' al-Sa'agh نفيع بن رافع أبو رافع الصائغ; al-Husain bin Mua'dh bin Khlyf الحسين بن معاذ بن خليف; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة (Sunan Abi Dawud)
I went out with the (Messenger of Allah (ﷺ) until I entered a garden, he said: Keep on closing the door. The door was then closed. I then said: Who is there ? He then narrated the rest of the tradition. Abu Dawud said: That is to say, the tradition of Abu Musa al-Ash’ari. In this version he said: “He then knocked at the door.”
Grade: Hasan